Reverse Engineering Approach for Customized Dental and Maxillofacial Implants of Alumina Fibre Reinforced Composite. (2019) - Mohanty, Saralasrita; Srivas, Pavan Kumar; Rameshbabu, Arun Prabhu; Saha, Partha; Dhara, Santanu
Abstract: Different customized implant fabrication processes are emerging with the advent of computer aided designing (CAD) and computer aided manufacturing (CAM) technologies to minimize bone removal during surgery and to facilitate faster recovery of the patients. In this direction, the present study offers an alternative reverse engineering approach towards development of customized oral and maxillofacial implants. Here, CAD model of dental crown and mandibular jaw were extracted directly from 3D scanned data and filtered using reverse engineering software. Using '.stl' file of the 3D model, prototype was developed by rapid tooling that was used for fabrication of customized flexible mold. Several difficulties and shrinkage associated defects were encountered during fabrication of alumina-based implants via molding technique. Finally, ceramic fiber reinforced epoxy-resin composite based implants (like mandible and dental crown) were successfully fabricated. The density and compressive strength of the composite were measured to be 0.95 g/cc and 369 MPa, respectively. The dimensions of the fabricated mandible and crowns were close to the natural one. The wear analysis revealed the significant differences in the volume loss between the composite (6.30x10 -5 cm 3 ) and human tooth (0.29x10 -5 cm 3 ) against composite. Besides fabrication related issues, the alumina fiber-reinforced epoxy resin composite has several other benefits like density, modulus match, improved tribology and cyto-compatibility.